PENGARUH TEKNOLOGI INFORMASI DAN SISTEM INFORMASI MANAJEMEN TERPADU TERHADAP KINERJA KARYAWAN DI LINGKUNGAN UNIVERSITAS WARMADEWA - Desak Made Arisuniarti (Public Inspiration : Jurnal Administrasi Publik, 2016)
Information Technology and SIM-T is a powerful tool to help the performance of employees within an institution that needs to be done research on it. This Research has 3 main objectives which are 1) identify the influence of information Technology in Warmadewa University, 2) to identify the influence of SIM-T to performance of Warmadewa University staff, 3) to identify the influence of TI & SIM-T implementation to the whole employee performance in Warmadewa University. The research has been conducted in Warmadewa University which involved the employees who able to operate computer and who understanding IT properly. Additionally, there were 3 objects involved which consisted of IT, SIM-T & employee performance. Primary data by quetionaire method has been compaited from 56 respondent which generated from slovin method & purposive sampling. The analysis showed that there were positive effects and significant results between IT and employee performance, SIM-T implementation to employee in Warmadewa University.Key Word: Information Technology, Integrated Management Information System dan Employee performance.